HUBUNGAN KEKUATAN OTOT QUADICEPS DENGAN KELISTRIKAN OTOT - Kurniawan, Ganesa Puput Dinda; Nasirudin, Yusuf; Ali, Mohammad; Pambudi, Restu Arya (Ikatan Fisioterapi Indonesia cabang kota bekasi, 2024)
The background of this study is to explore the relationship between quadriceps muscle strength and electromyographic muscle activity (EMG Surface), often assumed to correlate in physiological literature. Utilizing Spearman's rho statistical test and involving 53 participants, the study reveals a correlation value of 0.074 and a p-value of 0.600. These results indicate no significant relationship between the two variables. The findings provide important insights into the complexity of the interaction between muscle strength and EMG activity, highlighting the necessity of a holistic approach in muscle physiological research.